Desenvolvimento Social e Dimensões da Pobreza: Uma Análise do Índice de Desenvolvimento das Famílias (IDF) na Microrregião de Bocaiúva-MG - Fabrício Fontes de Andrade (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2009)
This article has as a center for discussion to analyze the process of social development from the perspective of quality of life, and the promotion of social-welfare, as well as if it searchs to approach the diverse dimensions of the poverty in view of the expansion of the freedoms human beings. Thus, synthetic pointer IDF is analyzed that accumulates of stocks diverse dimensions of the poverty, and social development while overcoming of the privations and difficulties of the life in society.